Influence of parents’ and caregivers’ characteristics on the outcomes of antiretroviral treatment in Ugandan children - Ntambwe Malangu (African Journal of Primary Health Care & Family Medicine, 2011)
Background: The purpose of this study was to investigate whether there was an association between characteristics of parents and caregivers, and the outcomes of antiretroviral treatment in children younger than 6 years treated at Mildmay Centre in Uganda. Methods: This study was a cross-sectional study based on the review of records. The records of children treated from January 2000 to July 2005 were included in the analysis as part of a larger study. Descriptive and inferential statistics were used in the analysis of data.